The best damn server virtualization book period - Buytaert, Kris.; Dittner, Rogier; Garcia, Juan R. (Burlington, Mass. : Syngress, 2007)
Server Sprawl and escalating IT costs have managers and system administrators scrambling to find ways to cut costs and reduce Total Cost of Ownership of their physical infrastructure. Combining software applications onto a single server, even if those applications are from the same software vendor, can be dangerous and problems hard to troubleshoot. Virtualization allows you to consolidate many servers onto a single physical server reducing hardware, electrical, cooling, and administrative costs. These virtual servers run completely independent of each other so if one crashes the other are not affected. Planning and implementing a server consolidation is a complex process. This book details the requirements for such a project, includes sample forms and templates, and delivers several physical to virtual migration strategies which will save both time and costs. Readers of this book will easily be able to plan and deploy VMware, Microsoft Virtual Server, and Xen. Key Features: * Create a virtual network to exchange information or provide a service to other virtual machines or computers. * Use virtualization to support removable media such as CD or DVD optical disks * Reduce server costs, administration overhead, and complexity.
VMWare Installation, Configuring a Virtual Machine, Gold Builds, and Clones, Advanced Configurations, Virtual Networking, Physical-to-Virtual Migrations, Server Consolidation, Cool Tools for a Virtual Infrastructure, Administering a Virtual Infrastructure, Best Practices, Gotchas and Common Problems, ESX Server: The Scripted Installation, Native Tools, Scripting and Programming for the Virtual Infrastructure, Building a VM, Modifying VMs, Installing and Configuring a Virtual Server, Virtual Machines, Virtual Networks, Virtual Disks, Introduction to ADS and Virtual Server Migration Tool, Managing Virtual Server, Migrating Physical Machines, Troubleshooting, Deploying Xen: Demystifying the Installation, The Administrator Console and Other Native Tools, Managing Xen with Third-Party Management Tools, Deploying a Virtual Machine in Xen.
Includes index.
Keywords: Client/server computing; Electronic books